2020
DOI: 10.3389/fphar.2020.00174
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Has a Therapeutic Effect via HIF Inhibition in a Murine Model of Choroidal Neovascularization

Abstract: Background: Lactoferrin, a type of glycoprotein, is contained in exocrine fluids such as tears, breast milk, sweat, and saliva, and is known to have anti-microbial, antioxidant, and anti-cancer effects. In the ophthalmological field, topical administration of lactoferrin has been reported to have a therapeutic effect in a murine dry eye model. Hypoxia-inducible factor (HIF) regulates various gene expressions under hypoxia, including vascular endothelial growth factor (VEGF), and is considered as an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…We examined whether AHX suppresses HIF downstream-target hypoxia-responsive gene expressions under CoCl 2 -induced hypoxic conditions ( Figure 3 ). After 6 h incubation of 200 µM CoCl 2 in 661W cells, the downregulation of Hif-1 α mRNA expression was detected due to a negative feedback from the post-translational HIF-1α protein modification ( Figure 3 A) [ 9 , 29 ]. We could not detect alteration of Hif-2 α mRNA expression ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We examined whether AHX suppresses HIF downstream-target hypoxia-responsive gene expressions under CoCl 2 -induced hypoxic conditions ( Figure 3 ). After 6 h incubation of 200 µM CoCl 2 in 661W cells, the downregulation of Hif-1 α mRNA expression was detected due to a negative feedback from the post-translational HIF-1α protein modification ( Figure 3 A) [ 9 , 29 ]. We could not detect alteration of Hif-2 α mRNA expression ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…We could not detect alteration of Hif-2 α mRNA expression ( Figure 3 B). CoCl 2 induced the upregulation of Vegf , Bnip3 and Pdk1 mRNA expressions as a result of HIF-1α activation ( Figure 3 C–E) [ 9 , 29 ]. The upregulated mRNA expressions, especially Vegf and Pdk1 , were suppressed by AHX treatment ( Figure 3 C,E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fold changes between levels of different transcripts were calculated by the ∆∆C T method. Protein extraction, electrophoresis and visualization of protein bands were performed as the same as previously described in our papers [15][16][17]20]. Antibodies used were anti-HIF-1α (1:1000, Cat #36169, Cell Signaling Technology, Danvers, MA, USA), anti-HIF-2α (1:1000, Cat #NB100-122, Novus Biologicals, Centennial, CO, USA) and anti-β-Actin (1:5000, #3700, Cell Signaling Technology, Danvers, MA, USA).…”
Section: Quantitative Pcr and Western Blottingmentioning
confidence: 99%
“…It has also been shown that lactoferrin, a type of glycoprotein, contained in exocrine fluids such as tears, breast milk, sweat and saliva, applied topically to the eyeball has a therapeutic effect in the mouse model of a dry eye. Studies have confirmed that the administration of lactoferrin had a significant inhibitory effect on HIF in retinal neuronal cells [10]. In 2019 search for new targeted therapies in the AMD studies also focus on genome editing by CRISPR/Cas9 viral delivery, which may include a new treatment option for inherited and acquired eye diseases.…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%